1991
DOI: 10.1056/nejm199111213252102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Octreotide on Intestinal Motility and Bacterial Overgrowth in Scleroderma

Abstract: Octreotide stimulates intestinal motility in normal subjects and in patients with scleroderma. In such patients, the short-term administration of octreotide reduces bacterial overgrowth and improves abdominal symptoms. This agent may be useful for the treatment of intestinal dysmotility in patients with scleroderma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
180
2
9

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(195 citation statements)
references
References 33 publications
4
180
2
9
Order By: Relevance
“…Appropriate caloric support must be provided by IV infusion. Erythromycin, somatostatin and neostigmine can be used to promote transit and decrease the duration of acute episodes [61][62][63] .…”
Section: Treatment Of the Acute Phasementioning
confidence: 99%
“…Appropriate caloric support must be provided by IV infusion. Erythromycin, somatostatin and neostigmine can be used to promote transit and decrease the duration of acute episodes [61][62][63] .…”
Section: Treatment Of the Acute Phasementioning
confidence: 99%
“…A role for motilin in the decreased intestinal motility in SSc remains purely speculative. It was observed recently that the somatostatin analog octreotide stimulates intestinal motility independently of the effects of motilin in patients with pseudoobstruction and bacterial overgrowth due to scleroderma (5). This indicates that other peptides may also be involved in SSc.…”
Section: Ma0 and Npymentioning
confidence: 99%
“…There is evidence of a defect in neurotransmitter release (3). Recent studies have shown that regulatory peptides act as neurotransmitters, and are involved in gastrointestinal motility, secretion, and absorption (4)(5)(6).…”
Section: Peptides Inmentioning
confidence: 99%
See 1 more Smart Citation
“…(21) Several studies have shown an association between dysfunction of intestinal motility and bacterial proliferation. (23)(24)(25)(26) In an experimental study Nieuwenhuijs et al compared infusion of morphine with placebo. Significant changes of intestinal motility were recorded in the group receiving morphine.…”
Section: Bacterial Translocationmentioning
confidence: 99%